VARIABILITAS CURAH HUJAN DI KABUPATEN KEBUMEN - Indratmoko, Satria; Harmantyo, Djoko; Kusratmoko, Eko (UI Scholars Hub, 2017)
Rainfall is highly variable climate elements, either in space or time scale. Variation of this rainfall will have an impact on the determination of the start of the planting of rice plants in particular. Through a statistical calculation and mapping of spatial data, this research will reveal a pattern of early growing season in response to rainfall variability in Kebumen Regency over a period of thirty years, i.e. 1981-2010. Spatial analysis with a reinforced approach statistics reveal that the coastal region in Kebumen Regency have a high rainfall variability with an average of rainfall is low. The higher the variability of annual precipitation totals declined, followed by the average rainfall is high. In addition, the beginning of paddy planting season begins in areas with low rainfall variability (the hills) to the region's high rainfall variability (coastal). In the period 1981-2000, paddy planting season begins early from the North and at regular intervals toward the South. On the other hand, in the period 2001-2010 paddy planting season begins early from the Northwest and at regular intervals toward the Southeast.